STRESS DISTRIBUTION COMPARISON OF IMPLANT FIXTURE-ABUTMENT CONNECTION TYPE AND ABUTMENT ANGLE VARIATIONS ON MANDIBLE FIRST MOLAR - Nadila Rahmaniar, Farah
Human teeth are essential for the use of grinding food inside the oral cavity for the purpose of swallowing and digesting food easier. If a tooth is damaged or lost, doing this function becomes harder. With dental implant, the mastication function can be restored. However, there are many things that could damage a dental implant. In this research, the fixture-abutment connection type and abutment angle variations are analyzed and compared from the side of stress distribution on the implant and surrounding bone. Each implant model from all variations are made using a 3D modelling software (SolidWorks) along with the bone surrounding the implant. The testing is done with static loading on a finite element software (Abaqus). After the loading test, the stress inflicted on each component are analyzed and compared betwen models to obtain the best variation of fixture-abutment connection type and abutment angle. The form of stress distributions on each variations don’t have much difference, but the maximum stresses occurring on each variations are different. Analyzing the highest stress occurring on each components yields the result as such; four petals is the best variation of fixture-abutment connection type; and for the abutment angle, 30° is the best angle.